A new method for selective reduction in TRAP sequence with a contraindication to fetoscopic surgery: A case report. Issue 10 (March 2017) - Li, Qi; Wu, Xin-Hua; Zhang, Wei-She
Abstract: Rationale: The preferred method for multifetal pregnancy reduction (MFPR) is a transabdominal intrathoracic or intracranial injection of potassium chloride (KCl). However, in monochorionic multiple pregnancies (MMPs), especially in monoamnionic multifetal pregnancies, selective feticide by this method is often associated with miscarriage of the remaining fetuses. Selective fetal reduction in MMPs by blood flow ablation using radiofrequency ablation or fetoscopic laser surgery may improve survival of the remaining fetus. Although often successful, MFPR by these methods is contraindicated in cases of twin reversed arterial perfusion (TRAP) sequence in triplet pregnancies complicated by polyhydramnios or anterior placenta, as it is difficult to locate the ablation target. Patient concerns: 2 cases were admitted to Xiangya Hospital, Central South University with triplet pregnancies at 23 or 21weeks of gestation. Diagnoses: Case 1 was a 29-year-old woman with a triplet pregnancy in 2 distinct amniotic sacs and 1 fetus with multiple malformations. Case 2 was a 32-year-old woman who was identified as a triplet pregnancy with TRAP sequence with an acardiac/acephalic twin and anterior placenta. Interventions: Both of the 2 cases were underwent a new method for MFPR involving fine needle amniotic fluid aspiration and injection of hypertonic sodium chloride (10% NaCl) into the Wharton jelly of the umbilical cord. Outcomes: The 2 cases resulted in selective feticide and the birth of the remaining infants from the triplet pregnancies. All infants were healthy at birth and the 2-year follow-up. Lessons: The new approach provided a safer, more accessible, and more cost-effective method for MFPR in MMPs with a contraindication to fetoscopic surgery compared to radiofrequency ablation and fetoscopic laser surgery.